The Role of Time Management in Achieving Creativity: A Field Study at Al - Aqsa University in the Gaza Strip - Palestine - AL Shair, Ezz El Din Mahmoud Abdel (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to identify the role of time management in achieving innovation at Al-Aqsa University in the Gaza Strip - Palestine through three time management strategies (targeting the aims, priorities, time planning and decision making) at Al-Aqsa University in the Gaza Strip - Palestine. And the relationship between the strategies of time management and innovation at Al-Aqsa University in the Gaza Strip - Palestine from the point of view of faculty members. The descriptive analysis approach was used. The research community consisted of heads of departments and academics at the faculties, units and centers at Al-Aqsa University. The data collection tool for the study was a questionnaire distributed to a random sample of 265 faculty members. The study reached several results, the most important of which is that time management has a role in achieving creativity at Al-Aqsa University in the Gaza Strip - Palestine, and that the availability of time management dimensions have a role in achieving creativity at Al-Aqsa University. The study showed that there is keenness among the sample members at Al-Aqsa University to plan early on their day-to-day work, low level of attention to long term goals and weak pursuit of these goals such acts, as well as there is less attention by the sample to predict the problems of work before they occur, and that faculty members at Al-Aqsa University have the ability to put forward ideas and solutions to address the problems fast.